Determination of the oxygen and nitrogen interstitial diffusion coeficient in niobium by mechanical spectroscopy - Florêncio, Odila; Silva Jr., Paulo Sergio da; Stefanini, Thais França; Grandini, Carlos Roberto [UNESP] (ABM, ABC, ABPol, 2006)
Mechanical spectroscopy measurements have been extensively used in the last decades to obtain information about many aspects of the behavior of solutes in metallic materials. Metals of body-centered cubic lattice that contain heavy interstitial elements (oxygen, nitrogen and carbon) in solid solution, present anelastic relaxation peaks when submitted to cyclic tensions, due to process know stress-induced ordering. Internal friction and frequency as a function of temperature were performed between 300 K and 650 K in a polycrystalline sample of Nb, for three distinct conditions, using a torsion pendulum inverted Kê-type operating in a frequency oscillation between 1Hz and 10 Hz range, with a heating rate of 1 K/min and pressure lower than 2 x 10-5 mbar. The experimental spectra obtained for each condition of the sample, were decomposed by the successive subtraction method in elementary Debye peaks. The following metal-interstitial interactions were identified: Nb-O and Nb-N for all conditions of the sample. From the anelastic relaxation parameters obtained (relaxation strength, peak temperature, activation energy and relaxation time) and lattice parameter (obtained from x ray diffraction), the determination of the oxygen and nitrogen interstitial diffusion coefficient in Nb was possible, for each condition of the sample.
Keywords: interstitial diffusion; niobium; internal friction; oxygen; nitrogen